2021
DOI: 10.33448/rsd-v10i15.23156
|View full text |Cite
|
Sign up to set email alerts
|

Perfil epidemiológico da Hanseníase no estado do Maranhão de 2018 a 2020

Abstract: Este estudo teve como objetivo analisar o perfil epidemiológico da Hanseníase no estado do Maranhão. Estudo transversal de caráter retrospectivo dos casos de hanseníase nos anos de 2018 a 2020 no estado do Maranhão, região nordeste do Brasil. Os dados foram obtidos por meio de consultas à base de dados do Sistema de Informações de Agravos de Notificação (SINAN), disponibilizados no Departamento de Informática do Sistema Único de Saúde (DATASUS). As variáveis utilizadas no estudo foram: macrorregiões de saúde, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
2
3
0
3
Order By: Relevance
“…The observed variation in the distribution of skin colors hints at a complex tapestry of migration and demographics in Brazil. These findings align with several other studies, including those conducted by Anjos et al [34], and Oliveira [40], wherein a predominant proportion of leprosy patients were of mixed-race backgrounds. This phenomenon can be attributed to Brazil's ethnically diverse composition resulting from extensive intermixing of ethnicities over time.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The observed variation in the distribution of skin colors hints at a complex tapestry of migration and demographics in Brazil. These findings align with several other studies, including those conducted by Anjos et al [34], and Oliveira [40], wherein a predominant proportion of leprosy patients were of mixed-race backgrounds. This phenomenon can be attributed to Brazil's ethnically diverse composition resulting from extensive intermixing of ethnicities over time.…”
Section: Discussionsupporting
confidence: 92%
“…It was observed that 60% of the patients were male, consistent with the predominance of affected men reported by Brasil [33] in the Epidemiological Bulletin on Leprosy. Additionally, PLOS NEGLECTED TROPICAL DISEASES Epidemiological, Clinical, and Geographical Characterization of Leprosy in Santare ´m-Para ṔLOS men often delay seeking healthcare, hindering the early interruption of the disease's clinical progression, resulting in late diagnosis and irreversible physical deformities [34].…”
Section: Discussionmentioning
confidence: 99%
“…Implementar medidas de recuperação e compensação psicológicas, assim como melhorar o ambiente de trabalho (DEMEROUTI, 2015;KALLIONIEMI et al, 2016;). Medidas como a pratica de exercicio fisíco na saúde mental, indicaram melhoras nos quadros de ansiedade e Burnout, em trabalhadores de diferentes areas, como saúde e setores administrativos (CUNHA et al, 2018;. Hábitos de vida saudáveis podem influenciar e reduzir agravos mentais e SB, em especial a prática de atividade física (AF), amplamente suportada na literatura como tratamento não-farmacológico de transtornos de humor (CUNHA et al, 2018;.…”
Section: Fundamentação Teóricaunclassified
“…Medidas como a pratica de exercicio fisíco na saúde mental, indicaram melhoras nos quadros de ansiedade e Burnout, em trabalhadores de diferentes areas, como saúde e setores administrativos (CUNHA et al, 2018;. Hábitos de vida saudáveis podem influenciar e reduzir agravos mentais e SB, em especial a prática de atividade física (AF), amplamente suportada na literatura como tratamento não-farmacológico de transtornos de humor (CUNHA et al, 2018;. Isto posto, o objetivo primário do presente trabalho foi identificar há associação entre os níveis de AF, qualidade de vida e domínios da SB em trabalhadores industriários de uma empresa de setor plástico…”
Section: Fundamentação Teóricaunclassified
“…4 , 5 It is possible that the significant reduction in cases observed in 2020 is due to the COVID-19 pandemic, which affected disease surveillance and control actions due to the overloading of health systems and services; or perhaps due to people’s movements from one place to another being restricted. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%